High infection rates of Toxoplasma gondii in cattle, sheep and pigs from Israel. (January 2023) - Mazuz, Monica Leszkowicz; Weiss, Adi; Beer, Oren; Tirosh-Levy, Sharon; Riklis, Irena; Dveyrin, Zeev; Rorman, Efrat; Cohen, Naama Zaaroor; Markovich, Michal Perry; Baneth, Gad
Abstract: Toxoplasma gondii is an obligate intracellular parasite belonging to the phylum Apicomplexa, which causes the zoonotic disease toxoplasmosis. T. gondii infects almost all warm blood animals. Generally, infected animals are asymptomatic and remain infected for life. Infection of humans occurs by consumption of infected undercooked meat or contaminated vegetables, fruit and water. The aim of this study was to evaluate the prevalence and seroprevalence of T. gondii in livestock in Israel. For the serological screening we investigated the presence of antibodies against T. gondii in sera using the indirect fluorescent antibody test (IFAT). Molecular screening was preformed using conventional PCR and nested PCR for the detection of T. gondii DNA in tissue samples. Serum samples of 249 cattle and 138 sheep were collected from farms. This serological survey showed high seroprevalence with seropositivity of 29 % in cattle and 33 % in sheep. In addition, 526 paired sera and tissue samples from cattle, sheep and pigs were obtained in slaughterhouses. The serological prevalence of T. gondii in healthy animals intended for human consumption was 29.4 % in cattle, 26.1 % in sheep and 8.1 % in pigs. The molecular detection of T. gondii in the tissue samples was 7.5 % in cattle, 7.3 % in sheep and 6.3 % in pigs. Considering the combined positive results from both serological and molecular assays, exposure to or infection with the parasite was present in 26.2 % of the samples (33.8 % in cattle, 30.3 % in sheep, 12.5 % in pigs). The prevalence of T. gondii in pigs was significantly lower compared to that of cattle and sheep (P < 0.001). All PCR positive samples from animals and 12 human positive samples were genotyped using a restriction fragment length polymorphism (PCR-RFLP) method. The results showed the existence of atypical genotypes in the majority of the samples and no correlation between animals and human samples could be determined from this study. Widespread exposure to T . gondii in Israel with the presence of parasite DNA in meat from cattle, sheep and pigs meant for human consumption was found. Highlights: High seroprevalence and molecular prevalence were observed in samples from cattle, sheep and pigs from slaughterhouses. The prevalence of T. gondii in pigs was significantly lower compared to that of cattle and sheep. The overall molecular prevalence in seropositive animals was significantly higher compared to seronegative ones. Atypical genotypes were observed in the majority of the examined samples.